PENINGKATAN KEMAMPUAN PENGGUNAAN GOOGLE GEMINI UNTUK PEMBELAJARAN DI SMK NEGERI 1 TANAH PINOH: PENDEKATAN PARTICIPATORY ACTION RESEARCH - Michael, Michael (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACT: This community service initiative aims to build the capacity of teachers and students at SMK Negeri 1 Tanah Pinoh to use Google Gemini technology for educational purposes. The programme adopts a participatory action research approach that involves several stages, including site survey, needs assessment, strategy development, training and implementation support. The target participants for this programme are teachers from SMK Negeri 1 Tanah Pinoh and SMK Negeri 1 Sokan, with a total of 50 participants. Throughout the programme, teachers will be trained to use open module design and to integrate technology in the classroom. Data is collected through surveys, interviews and focus group discussions (FGDs). Formative and summative evaluations show that teachers are able to use Google Gemini to create more creative and innovative teaching modules. The quality of teaching modules has improved and teachers are more motivated to use AI technology in their teaching through the Gemini. For future community service activities, regular evaluations are recommended to assess the long-term impact of technology integration in the teaching and learning process..Keywords: Gemini, Learning, Participatory Action ResearchABSTRAK: Kegiatan pengabdian ini bertujuan untuk meningkatkan kemampuan guru dan siswa SMK Negeri 1 Tanah Pinoh dalam memanfaatkan teknologi Google Gemini untuk pembelajaran. Pengabdian ini menggunakan pendekatan Participatory Action Research, yang mencakup beberapa tahapan, yaitu survei lokasi, identifikasi kebutuhan, pengembangan strategi, pelatihan, dan pendampingan implementasi. Sasaran kegiatan ini adalah guru SMK Negeri 1 Tanah Pinoh dan SMK Negeri 1 Sokan, dengan total peserta sebanyak 50 orang. Dalam kegiatan ini, para guru dilatih untuk menggunakan desain modul terbuka dan mengintegrasikan teknologi ke dalam pembelajaran di kelas. Data dikumpulkan melalui survei, wawancara, dan diskusi kelompok terfokus (FGD). Hasil evaluasi formatif dan sumatif menunjukkan bahwa para guru mampu memanfaatkan Google Gemini untuk membuat modul ajar yang lebih kreatif dan inovatif. Kualitas modul ajar yang dihasilkan meningkat, dan guru menjadi lebih termotivasi untuk mengadopsi teknologi AI dalam pembelajaran melalui Gemini. Untuk kegiatan pengabdian berikutnya dapt dilakukan evaluasi berkala untuk menilai dampak jangka panjang penerapan teknologi dalam pembelajaran.Kata Kunci: Gemini, Pembelajaran, Participatory Action Research